ANALISIS ANTISIPASI RISIKO DALAM MENINGKATKAN HASIL PRODUKSI KEBUN KELAPA SAWIT PADA PTPN VI UNIT USAHA RISMA KABUPATEN TEBO - Ira widyastuti; Hasdani Hasdani; Ha Esdhona; Muhammad Nasir (Institut Administrasi dan Kesehatan Setih Setio, 2023)
In this research, the author examines the analysis of risk anticipation increasing to production of palm oil plantations.Business risk is the impact that must be borne by business people as a result of the gap between expectations and reality faced, or between what has been planned and its realization. Human resources and fertilization period are also very important to increase yields of good quality. Obstacles in increasing the production of palm oil plantations are disruption of fertilizing palm oil trees due to weather changes, often running out of stock, and fertilization that is still traditional.This study aims to find out how to efforts make increase the production of palm oil plantations. The populations in this study are company managers, all employees of PTPN VI Rimsa Unit, Tebo Regency. The sampling technique uses a purposive sampling technique, which a sampling technique that is carried out based on characteristics that are adjusted to the objectives or research problems. The sample in this study consisted of 10 people, namely the manager, assistant head, assistant afd 3, foreman 1 afd 3,? 2 (two) harvest foremen, and 4 (four) workers in the palm oil fertilization division of PTPN VI Rimsa Unit, Tebo Regency.Based on the researched result, PTPN VI Rimsa unit, Tebo regency has implemented several efforts to increase the production of palm oil plantations, namely: the company's part must estimate the time for the fertilization process when the intensity of rainfall is light and how to budget for fertilizer to suit the needs of palm oil, and the company must have other alternatives to avoid delays in fertilizer stocks, must make the most of manpower.